Distribution of Potentially Pathogenic Vibrio parahaemolyticus in Seafood and the Aquatic Environment of Mumbai, India - Ayyappan, Minimol V.; Balange, Amjad K.; Nayak, Binaya Bhusan; Kumar, Sanath (Fishery Technology, 2018)
The occurrence of total and pathogenic Vibrioparahaemolyticus in fresh seafood and the coastalenvironment of Mumbai, India was examined in thisstudy. Samples comprising of fish, shellfish, coastalsediment and coastal waters were analyzed forV. parahaemolyticus by selective enrichment andisolation. Biochemically identified isolates weretested for the presence of tlh (thermolabile hemolysin),tdh (thermostable direct hemolysin) and trh(tdh-related hemolysin) by polymerase chain reaction(PCR). While Chromogenic Vibrio (CV) agaryielded V. parhaemolyticus from all samples (100%),TCBS agar yielded V. parahaemolyticus from 57.1% ofthe samples. The incidence of trh+ V. parahaemolyticuswas high, being isolated from 16.4% of the samplesanalyzed, while the tdh+ V. parahaemolyticus wereisolated from 1.4% of samples. Two tdh-, trh+ isolatesfrom the coastal water were positive by a inpandemic group-specific (GS) PCR. The studysuggests that seafood and coastal environment mayharbor pathogenic V. parahaemolyticus with characteristicsof pandemic clones, although their incidenceis very low. Further, sodium taurocholate(ST) broth and chromogenic Vibrio (CV) agarcombination is highly suitable for the isolation oftotal and pathogenic V. parahaemolyticus from seafoodand environmental samples.